The Energy Density of the Universe in the Vector Model for Gravitational Field
We show that, in the framework of the vector model of gravitational field, the total mass density and the mass of the Universe are quite the same as of experimental observed ones \(ρ_total 1.0 × 10^−29\) g/cm\(^3\) and \(M_universe 1053\) kg., number=1, journal=Communications in Physics, author=On, Vo Van, year=2019, month=Aug., pages=13–16